Perancangan SPK Dalam Penentuan Kelayakan Perpanjangan Kontrak Kerja Karyawan PT.WBL Devisi Operasional Menggunakan Metode Profile Matching - B, Muslimin; Rowa, Heruzulkifli (INFOTEKS (Information Technology, Computer and Sciences), 2020)
Private companies currently tend to implement contract systems in all divisions and subdivisions. PT.Wulandari Bangun Laksana(WBL)/ Balikpapan Super Block(BSB) operational scope of the implementation of the contract recruitment system up to several times the contract extension so that the employee is eligible to be appointed as permanent employees. During the extension of the work contract, the operational supervisory supervisor carries out an analysis process in determining the eligibility of employees to be accepted as permanent employees. In order to produce the expected assessment, a mechanism and modeling process is needed that can be processed by a system and evaluation and analysis process carried out by the operational supervisor. This study aims to build a decision support system in determining the feasibility of extending the PT.WBL/Balikpapan Super Block(BSB) employee contract based on good and effective performance objectively using the profile matching method. Decision support system is a technique for using the system in managing the evaluation process by the decision maker (supervisor). The implementation of the profile matching method is the application of a method that can handle the appraisal process based on evaluation of criteria and the value of preferences towards employee alternatives. The data processed is employee data in the scope of the operational division Balikapan Super Block(BSB). The results of the evaluation carried out produce an alternative weight of employees, which can be used as consideration in making decisions on the feasibility of extending the work contract or being appointed as permanent employees. Based on the evaluation process of the criteria and alternatives carried out, it is expected to produce decision values ​​and modeling processes with high accuracy values.